Environmental Impacts Of The Oil And Gas Platform Decommissioning - R Desrina; Chairil Anwar; Tri Muji Susantoro (Scientific Contributions Oil and Gas, 2013)
Many of the oil and gas installations in the Indonesian Sea are reaching the end of their economic production life. Typically, oil and gas fields have an economic life of 20 to 40 years and a decommissioning program will be required and predicted to peak during the period 2010-2020. Some of them are located in shallow water such as those around Pulau Seribu, Java Sea, and South China Sea; some others are in deeper water such those at Makasar Straits and Moluccas Sea. Many different opinions exist on the benefits and problems of a partial platform removal or a complete removal. For some reasons platforms would be a good fishing spot. On the other hands, an unseen hazard could be left behind by the platforms. Even a complete removal of the platforms is conducted but without proper clearing of the ocean floor, the unused platforms still can cause hazards. For the management of the seas outside the territorial waters, worldwide nations have historically entered into international agreements and conventions. These agreements and conventions that have been entered into under the umbrella of the United Nations are Geneva Convention, the United Nations Convention on the Law of the Sea (UNCLOS) and the International Maritime Organization (IMO) Guidelines. Nationally, there is little information concerning with the decommissioning project. This paper is intended to highlight options for decommissioning of offshore platforms, its environmental impacts, and regulations that could be referred to following the decommissioning proposal. The technological aspects of the structural decommissioning of platforms are beyond the scope of this paper. Â